2021
DOI: 10.14423/smj.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Orthopedic Surgeons: Elective Procedures, Telehealth, and Income

Abstract: This document contains the image that you requested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
11
1
1
Order By: Relevance
“…Mavrogenis et al demonstrated that throughout the COVID-19 pandemic, nearly 98% of all orthopaedic surgeons suffered some monetary impact( 26 ). Paul et al demonstrated the financial losses to orthopaedic surgeons, noting that the highest impacted states included Alabama, Georgia, and Missouri( 27 ). In a survey of Louisiana Orthopaedic Association members, Kale et al demonstrated that a majority of surgeons had applied for government assistance or took out loans during COVID-19 to support practice, personnel, and overhead costs( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mavrogenis et al demonstrated that throughout the COVID-19 pandemic, nearly 98% of all orthopaedic surgeons suffered some monetary impact( 26 ). Paul et al demonstrated the financial losses to orthopaedic surgeons, noting that the highest impacted states included Alabama, Georgia, and Missouri( 27 ). In a survey of Louisiana Orthopaedic Association members, Kale et al demonstrated that a majority of surgeons had applied for government assistance or took out loans during COVID-19 to support practice, personnel, and overhead costs( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…They will also avoid going to the hospital for fear of possible infection with COVID-19. Although there are undoubtedly some injuries requiring urgent treatment, telemedicine or virtual consultation may be a good alternative option to provide rapid and safe healthcare services in some countries [ 24 , 27 , 28 , 30 , 35 , 48 ]. Teo et al reported that 19.3% of orthopedic surgeons started to use telemedicine owing to COVID-19 in Malaysia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic surgeons’ incomes changed during COVID-19 pandemic [ 10 , 14 , 15 ]. The rapidly spreading threat imposed an unprecedented burden on the effectiveness and sustainability of the healthcare systems.…”
Section: Orthopedic Practice In Covid-19 Pandemicmentioning
confidence: 99%
“…However, although it might work for a tendinitis or carpal tunnel syndrome, it cannot be useful if the patient has a fracture. It is our opinion that the use of telemedicine will continue in the post-pandemic era; yet, telemedicine may facilitate the care but does not appear to replace in-person clinics [ 15 , 16 ]. Virtual clinics should be expected to benefit the patients.…”
Section: Orthopedic Practice In Covid-19 Pandemicmentioning
confidence: 99%